Spread of the Sindbis Virus in Fennoscandia - L. V. Rubis; Л. В. Рубис (Russian Research Anti-Plague Institute “Microbe”, 2023)
In the second half of the last century, a persistent focus of the disease caused by Sindbis virus was formed on the territory of Fennoscandia. In different countries, the disease is called Pogosta disease, Ockelbo disease and Karelian fever. The highest incidence rate is in Finland, where diseases are recorded annually, ranging from sporadic cases to large outbreaks with hundreds of patients. In other Scandinavian countries and in Russia, isolated cases of infection are currently being detected. The data on registered incidence and the results of seroepidemiological studies indicate an unequal dissemination of the infection in Fennoscandia, the causes of which need to be investigated. The review presents updated information on the pathogen, its distribution among the population and in the biocenosis of Fennoscandia, clinical features, diagnostics and epidemiological characteristics of the incidence. Во второй половине прошлого века на территории Фенноскандии сформировался стойкий очаг заболеваний, вызываемых вирусом Синдбис. В разных странах заболевание получило названия «болезнь Погоста», «болезнь Окельбо» и «карельская лихорадка». Наиболее высокая заболеваемость – в Финляндии, где заболевания регистрируются ежегодно в диапазоне от спорадических случаев до крупных вспышек с сотнями пострадавших. В других странах Скандинавии и в России в настоящее время выявляются единичные случаи инфекции. Данные о регистрируемой заболеваемости и результаты сероэпидемиологических исследований свидетельствуют о неравномерном распространении инфекции на территории Фенноскандии, причины которого требуют изучения. В статье приведены современные данные о возбудителе, его распространении среди населения и в биоценозе Фенноскандии, клинических особенностях, диагностике и эпидемиологических характеристиках заболеваемости.